THE INFLUENCE OF SERVICE QUALITY, PRODUCT ATTRIBUTES, AND COMPANY REPUTATION THAT AFFECT CONSUMER BUYING INTEREST - Dicky Zulkarnain; Sulaiman Helmi (SEAN Institute, 2023)
This study investigates the importance of the influence of service quality, product attributes, and company reputation on consumer repurchase intentions in a business and marketing context. The aim is to analyze how these factors interact and influence consumer repurchase intention. This research method involves collecting data through surveys of respondents who are consumers from various industrial sectors. Data analysis was performed using a statistical approach and a regression model. The findings show that service quality has a significant effect on consumer repurchase intention, as well as a positive effect on company reputation. In addition, product attributes also have a strong impact on consumer repurchase intentions and have a positive effect on company reputation. Company reputation is proven to have a significant influence on consumer repurchase intention. In conclusion, the factors of service quality, product attributes, and company reputation together play an important role in shaping consumer repurchase intention. These findings provide strategic insights for practitioners in designing marketing strategies that focus on strengthening service quality, attractive product attributes, and a positive company image to increase consumer repurchase interest and maintain a competitive market share.